Smart Car Parking System on FPGA For Time Efficient - Kasivishva Nathan, Sharma Kumar; Ahmad, NorNabihah (Evolution in Electrical and Electronic Engineering, 2023)
This project is a smart parking system that uses infrared sensors and a Field Programmable Gate Array (FPGA) to improve the efficiency and convenience of finding parking in urban areas. The system uses a network of sensors to detect the presence of vehicles in a parking garage and LED lights to show parking space availability. The FPGA processes the sensor data in real time and executes parking algorithms for fast and accurate results. The parking system was tested by simulating and by setting up a prototype and showed promising results with a high success rate in detecting parking spaces. The use of IR sensors and LED lights makes for a cost-effective and energy-efficient design. The FPGA technology allows for flexibility and scalability, making it well-suited for use in smart parking systems. The prototype represents a small-scale implementation of the system, showcasing two levels of parking, each with four parking spaces. The LED lights indicate available parking spaces and a display shows the total number of occupied spaces. This prototype represents a proof of concept and can be developed further for large-scale implementations. The smart parking system has the potential to significantly improve the efficiency and convenience of parking in urban areas. The prototype is checked and tested by using toy cars to check on the smart parking system.